2019
DOI: 10.1186/s40248-019-0203-6
|View full text |Cite
|
Sign up to set email alerts
|

Focus on the cetirizine use in clinical practice: a reappraisal 30 years later

Abstract: Antihistamines are currently one of the most commonly administered categories of drugs. They are used to treat symptoms that are secondary to histamine release, which is typical of certain allergic conditions, including rhinitis, conjunctivitis, asthma, urticaria, and anaphylaxis. Cetirizine belongs to the second-generation family, so, it is very selective for peripheral H1 receptors, is potent and quickly relieves symptoms, exerts additional anti-allergic/anti-inflammatory effects, and is usually well-tolerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…One study suggested diphenhydramine, hydroxyzine, and azelastine to be considered in repositioning, then further research in them. 17 Due to its potent, less side effects, rapid onset of action, specificity, antiallergic, and anti‐inflammatory properties, 24 Cetirizine might be an important drug of consideration in managing Covid‐19 patients at the moment compared to other antihistamines or histamine receptors (H2, H3, and H4).…”
Section: Role Of Antihistaminesmentioning
confidence: 99%
“…One study suggested diphenhydramine, hydroxyzine, and azelastine to be considered in repositioning, then further research in them. 17 Due to its potent, less side effects, rapid onset of action, specificity, antiallergic, and anti‐inflammatory properties, 24 Cetirizine might be an important drug of consideration in managing Covid‐19 patients at the moment compared to other antihistamines or histamine receptors (H2, H3, and H4).…”
Section: Role Of Antihistaminesmentioning
confidence: 99%
“…Subyektifnya adalah gatal pada tangan dan ruam kemerahan. Obat yang disarankan oleh apoteker adalah Cetrizine HCl 10 mg sehari 1×1 tablet diberikan sebagai aktivitas antihistamin, efek utamanya dicapai melalui penghambatan selektif reseptor H1 perifer [12,13]. Pencegahan alergi disarankan untuk mencoba mengidentifikasi apa yang menyebakan alergi, apa yang dimakan, kapan gejala muncul dan apa yang membantu pemicu.…”
Section: Kasus Ke-3unclassified
“…Second-generation antihistamines should be, therefore, used to control nasal and ocular itching. Effective and safe oral medications should be preferred, such as well-proven molecules, such as cetirizine, loratadine, and fexofenadine, to relieve nasal and ocular complaints [3][4][5].…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…Depending on the age of the child and the food/foods that are eliminated, nutritional deficiencies may arise [2,13]. Specific micronutrients, including vitamins A, D, C, E, B6, and B12, folate, zinc, iron, copper, and selenium, have a synergistic role in the immune response [3]. Malnutrition can compromise the proper functioning of the immune system [2,[13][14][15][16][17].…”
Section: Food Allergymentioning
confidence: 99%